The Effectiveness of the STEAM Approach on Critical Thinking Skills in Science and Scientific Attitudes in IPAS Learning in Primary Schools - Halimah, Siti; Nurulpaik, Iik; Supriatna, Encep (Papanda Publisher, 2025)
The integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) education has emerged as a promising approach for developing 21st-century skills, yet empirical evidence of its effectiveness in primary education remains limited. This study investigated the effectiveness of STEAM approaches on critical thinking skills and scientific attitudes in Natural and Social Sciences (IPAS) learning among elementary school students. A quasi-experimental design with nonequivalent group posttest-only was employed involving 64 fifth-grade students at SDN Patrasana 1 during the 2024/2025 academic year. Participants were divided into experimental (n=32) and control (n=32) groups using purposive sampling based on equivalent baseline performance. The experimental group received STEAM-based instruction while the control group experienced conventional teaching methods. Data collection utilized validated instruments measuring critical thinking skills and scientific attitudes, supplemented by observation and documentation. Statistical analyses included normality testing, homogeneity assessment, MANOVA, and hypothesis testing using SPSS 27. The STEAM approach demonstrated statistically significant effects on both critical thinking skills (F = 14.861, p < 0.001) and scientific attitudes (F = 9.991, p = 0.002). Multivariate analysis confirmed simultaneous positive effects on both variables (p = 0.001). The STEAM approach explained 19.3% of variance in critical thinking skills and 13.9% of variance in scientific attitudes, indicating meaningful practical significance. These findings provide robust empirical evidence supporting STEAM education effectiveness in primary contexts, addressing a critical knowledge gap in educational research. The results validate theoretical frameworks emphasizing integrated approaches while demonstrating that STEAM implementation can successfully develop multiple learning dimensions simultaneously, supporting early intervention strategies for 21st-century skill development.